Geological Histories from 4372 Ma to 26 Ma Recorded in Siliciclastic Metasedimentary Rocks from the Central Yilgarn Craton - Thern, Eric Royal (Curtin University, 2012)
This study presents an investigation of detrital, metamorphic, and hydrothermal minerals from siliciclastic metasedimentary rocks of the Illaara and Maynard Hills greenstone belts, central Yilgarn Craton. This research assesses how 4.3 to 3.0 Ga detrital zircon populations came to be found in dispersed metasedimentary rocks, how these rock occurrences relate to each other and what this may reveal about the early Earth and the formation of the Yilgarn Craton.